The use of probiotic in the diet to improve carcass characteristics and meat quality of sheep - Haryanto, Budi (Indonesian Journal of Animal and Veterinary Sciences, 2000)
An experiment has been carried out to investigate the effect of probiotic and ruminally less-degradable protein supplementation on the growth and efficiency of feed utilization in sheep. Thirty two male sheep with an average liveweight of 23 kg were divided into 4 groups of 8 individuals to test four dietary treatments. The dietary treatments were a) basal concentrate diet, b) basal concentrate diet supplemented with ruminally less degradable protein in proportion of 90:10%, c) basal concentrate supplemented with probiotic at 0.5%, and d) basal concentrate diet supplemented with ruminally less degradable protein and probiotic in proportion of 89.5:10:0.5% consequtively. The concentrate was fed at 1.5% of the liveweight, and adjusted every week after weighing the individuals. Napier grass was fed ad libitum after being chopped into 5 cm length. Drinking water was available adequately. The animals were individually caged. The experiment was carried out for 7-day adaptation to the dietary treatments and 42-day period of feeding trials. The parameters being observed include weekly liveweight changes, slaughter weight, carcass weight and carcass characteristics. The results indicated that the liveweight changes were relatively the same for all treatment groups, which ranged from 89 to 94 g/d. However, the dry matter intakes ranged from 856 to 925 g/d. The slaughter weight ranged from 26.9 to 27.3 kg with carcass weight ranged from 12.0 to 12.8 kg indicating that the carcass percentage were in the range from 55.8 to 57.1% of the empty body weight. Probiotic supplement resulted in reduction of fat content in the meat from these observation, it is reasonable to assume that the use of probiotic in the diet reduced the carcass fat without affecting the daily weight gain. Â  Key words: Sheep, probiotics, ruminally less-degradable protein, productivity.